Poaching and firm-sponsored training: First clean evidence - Jens Mohrenweiser; Thomas Zwick; Uschi Backes-Gellner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
A series of seminal theoretical papers argues that poaching of employees may hamper company-sponsored general training. However, the extent of poaching, its determinants and consequences, remains an open empirical question. We provide a novel empirical identification strategy for poaching and investigate its causes and consequences. We find that only a small number of training firms in Germany are poaching victims. Firms are more likely to poach employees during an economic downturn. Training firms respond to poaching by lowering the share of new apprentice intakes in the following years.
urn:nbn:de:bsz:180-madoc-339137
Keywords: J24; M51; M53; 330; poaching; company sponsored training; recruiting; apprenticeship